The context of application of biosecurity for control of African swine fever in smallholder pig systems: Current gaps and recommendations - Mutua, Florence K.; Dione, Michel M. (Frontiers Media, 2021)
African swine fever (ASF) is a highly fatal disease of pigs. It is a threat to the pig industry as it lowers production and significantly impacts on livelihoods. ASF has no cure and a vaccine against it is yet to be developed. Outbreaks continue to be reported in Africa and Asia, where the setting of the pig value chain (farm, market, and slaughter practices) coupled with the risky behaviors of actors, contribute to persistence of the virus in pig populations. The role of these factors in the epidemiology of the disease is reviewed with a focus on smallholder pig systems in Africa. Biosecurity at the farm level is particularly emphasized, and factors influencing its adoption highlighted. Socio-cultural factors and weaknesses at the disease control policy level are critical and should not be ignored. Gender and equity are important aspects and ought to be considered in discussions to improve the sector. The findings are expected to define priorities for interventions to improve pig productivity (as these regions wait for the vaccine to be developed).